2020
DOI: 10.3390/cryst10050407
|View full text |Cite
|
Sign up to set email alerts
|

Role of Potassium Substitution in the Magnetic Properties and Magnetocaloric Effect in La0.8−xKxBa0.05Sr0.15MnO3 (0 ≤ x ≤ 0.20)

Abstract: The magnetic and magnetocaloric effects of potassium-substituted La0.8−xKxBa0.05Sr0.15MnO3 (0 ≤ x ≤ 0.20) manganite were explored. The samples in polycrystalline form were synthesized by the sol–gel method, with a final sintering temperature of 1100 °C. Powder X-ray diffraction (XRD) patterns refined by Rietveld refinement show that all samples crystallized in rhombohedral structure with R-3c space group. The unit cell volume of the samples decreases with increasing potassium concentration. In addition, small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…To estimate its size, a formulation has been proposed as defined below. 17 〈 r A 〉 = Σ x i r i where, 〈 r A 〉 is the average ion radius size, x i is the ion content in the system, and r i is the ion radius size in the system. Fig.…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate its size, a formulation has been proposed as defined below. 17 〈 r A 〉 = Σ x i r i where, 〈 r A 〉 is the average ion radius size, x i is the ion content in the system, and r i is the ion radius size in the system. Fig.…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 99%
“…48 Additionally, Razaq et al reported that La 0.8 K 0.1 Ba 0.05 Sr 0.15 MnO 3 has a t value of 0.965, displaying a rhombohedral structures. 17…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…; Tm in TmZn [198] and metallic glasses [233]; rare earth in clathrates [277,296], etc. Manganites [258] include La 0.7 Ca 0.3 MnO 3 [227,262,264,285], La 0.48 Ca 0.52 MnO 3 [174], Na-deficient La 0.8 Na 0.2−x MnO 3 [185], La 0.67 Sr 0.16 Ca 0.17 MnO 3 [207], La 0.8−x K x Ba 0.05 Sr 0.15 MnO 3 [297], as well as containing critical rare earth La 0.7−x Pr x Ca 0.3 MnO 3 [160], GdMnO 3 [186], Gd 2 NiMnO 6 and Gd 2 CoMnO 6 [193], TbMnO 3 [165,252], DyMnO 3 [247], PrPb manganites [294], etc. Materials containing highly toxic arsenic include MnAs [123,131,210,238,245,246,256,265,273,276,282,289] and MnFe(P,As) [48,49,239,298].…”
Section: ∆S T T C (K) ∆T S (K)mentioning
confidence: 99%
“…The CMR effect in perovskite rare earth manganates can lead to significant changes in the electrical resistivity of these materials in response to magnetic fields. The double exchange mechanism, first introduced by Zener in 1951 [19], is the underlying mechanism that causes this effect. The CMR effect can be classified into two categories: intrinsic CMR and extrinsic CMR.…”
Section: Introductionmentioning
confidence: 99%